2008
DOI: 10.1037/a0013741
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the cognitive-stress model of depressive symptoms in adolescents.

Abstract: This prospective study investigated a cognitive diathesis–stress model of depression in adolescents across the transition from 6th to 7th grade using individual, additive, weakest link, and keystone approaches to operationalizing the cognitive vulnerability. Participants were 240 young adolescents (mean age = 11.87 years, SD = 0.57) who differed in risk for mood disorders based on their mother’s history of depression. Results of the hierarchical multiple regression analyses indicated some support for the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 175 publications
8
43
0
2
Order By: Relevance
“…The higher the positive score, the more optimistic the attributional style was. In this sample, Cronbach's alpha coef fi cients for positive events were moderate (.36 for Romanian, .43 for Hungarian adolescents from Banat and .31 for Romanian adolescents from Moldova) and similar with the internal consistencies reported in other studies (Morris et al 2008 ;Thompson et al 1998 ) .…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…The higher the positive score, the more optimistic the attributional style was. In this sample, Cronbach's alpha coef fi cients for positive events were moderate (.36 for Romanian, .43 for Hungarian adolescents from Banat and .31 for Romanian adolescents from Moldova) and similar with the internal consistencies reported in other studies (Morris et al 2008 ;Thompson et al 1998 ) .…”
Section: Methodssupporting
confidence: 81%
“…Total scores range from 0 to 54, with higher scores indicating greater symptom severity. The CDI has a good internal consistency and convergent validity with other self-report measures (Abela et al 2007 ;Morris et al 2008 ) . The alpha coef fi cients for the CDI ranged from .53 to .61 across all samples.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, whereas, some studies among adolescents have suggested that inferential styles are more likely to moderate the relation between negative life events and depressive symptoms in girls than boys (Abela 2001;Abela and McGirr 2007), other studies have found the reverse pattern Morris et al 2008). In contrast, the few other studies examining sex moderation have not yielded significant effects in adolescents (Abela 2002;Hankin 2008) or college students (Abela and Seligman 2000).…”
Section: Introductionmentioning
confidence: 90%
“…Estévez y Calvete, 2009;Morris, Ciesla y Garber, 2008). Dado que es una teoría de diáthesis-estrés, la investigación se ha centrado en dos aspectos fundamentales: por una parte, se han tratado de confirmar los componentes presentes en la relación entre la diá-thesis (esquemas cognitivos vulnerables, depresivos) y el estrés ocasionado por situaciones vitales negativas, aversivas (Auerbach, Eberhart y Abela, 2010).…”
Section: Introductionunclassified